New beef burger formulation with added cherry (pico negro variety) as a potential functional ingredient - María Jesús Martín-Mateos; Alberto Ortiz; Palmira Curbelo; Carmen Barraso; Lucia León; María Montaña López-Parra; David Tejerina; Susana García-Torres (Applied Food Research, 2022)
Abtract: Consumers are increasingly interested in healthy food and meat products with new health attributes, such as natural antioxidants and dietary fibre. This study attempts to investigate the effects of using different proportions of cherries (pico negro variety) as a natural ingredient on the physical-chemical and sensorial characteristics of meat burgers. The results indicated that as the proportion of cherries that were added to the formulation of beef burgers increased, the nutritive content was modified and the caloric content decreased. The increasing addition of cherry, with high antioxidant content, increased the antioxidant activity of the burgers, which had a protective effect on protein oxidation. Textural properties were not affected by cherry addition when this was evaluated using the instrumental method and a sensorial panel, which detected higher color intensity and lower meat flavour intensity with higher proportions of cherry in the burgers. The most preferred burger was the cherry 2% burger, whilst the first choice for raw burgers was the burger with the highest cherry content.